Characterizing the structural and physicochemical properties of medicinal plants as a proposal for treating of viral malady - Mollaamin, Fatemeh (Trends in Immunotherapy, 2023)
Regarding coronavirus disease (COVID-19) pandemic, this research article wants to study some herbals as the probable therapy for this disease. Cinnamon leaves, curcuma longa (turmeric), ginger, mentha pulegium (pennyroyal), rosemary, salvia divinorum and thyme including some principal chemical compounds of cynnamil, curcumin, gingerol, pulegone, rosmarinic acid, salvinorina A and thymol, respectively, as a probable anti COVID-19 receptor have been selected. The possible roles of these medicinal plants in COVID-19 treatment have been carried out through quantum sensing methods. Formation of hydrogen bonding between principal substances selected in COVID-19 natural drugs bound to Tyrosine-Methionine-Histidine (Tyr-Met-His) or (TMH) (the database amino acids fragment) as the active area of the COVID-19 protein has been evaluated. In fact, it has been exhibited the role of oxygen, nitrogen, and hydrogen atoms in the active sites of these anti-virus medications towards hydrogen bonding in the active site if “TMH” protein. The physical and chemical attributes of nuclear magnetic resonance, vibrational frequency, the highest occupied molecular orbital energy and the lowest unoccupied molecular orbital energy, partial charges and spin density and have been accomplished using density functional theory (DFT) method and 6-311+G (2d,p) basis set by Gaussian 16 revision C.01 program toward the industry of drug design. This research has exhibited that there is a relative agreement among the results that these medicinal plants could be efficient against COVID-19 symptoms